Principles of Agile Governance in Digitalization Tourism Villages: Studies on E-lok in the Sambirejo Tourism Village - Sabarna Muhammad Akbar Nugraha; Purnomo Eko Priyo; Khairunnisa Tiara (E3S Web of Conferences)
This study aims to determine the Principles of Agile Governance in the Digitalization of Tourism Villages. This research takes a case study in Sambirejo Village, Sleman, Special Region of Yogyakarta, as one of the villages that has implemented the principles of Agile Governance in the form of E-Loket as a form of digitizing Tourism Villages. The method used in this study is a qualitative descriptive research type, with the main data obtained from several mass media such as online news. The data obtained was also analyzed by software analysis with the crosstab feature in NVivo 12 plus. In addition, the data were analyzed using interactive model techniques through three aspects of analysis, including: data reduction, presentation and conclusion. The theoretical basis used in this study is to use three (3) principles of agile governance put forward by Luna, Krutchen, and Moura: Based on Quick Wins, Human Focused, Simple design and continuous improvement. So that the results of the research can find out the principles of Agile Governance in the Digitalization of tourist villages: Studies on E-lok of the Sambirejo Tourism Village.